A current-balancing circuit for multiple light-emitting-diode (LED) strings - Huang, Jiayi (Nanyang Technological University, 2023)
Light Emitting Diodes (LEDs) are one of the most widely used lighting devices in a multitude of applications, from light indicators on electronic devices to street light lamps. They serve as an important replacement for older lighting methods, such as incandescent and fluorescent lights. LEDs can be compact, have energy efficient properties and longer lifespans compared to their conventional lighting counterparts. Therefore, these advantages allow it to have the benefits of being more cost effective and sustainable.